Construct validation of lower limb segmental excursion as a measure of potential risk for lower limb injury in Division I women's basketball players. (14th February 2019) - Gaunaurd, Ignacio; Kim, Kyoung Jae; Feigenbaum, Luis; Raya, Michele; Baraga, Michael; Fontela, Natalie; Gailey, Robert
Abstract: The region of limb stability (ROLS) is an inertial sensor-based measure of static knee joint stability, defined by thigh and shank movements of the supporting limb during single limb stance. Changes in thigh and shank movements and/or symmetry differences between limbs may predict risk of injury to the less stable limb or the need for rehabilitation. In this study, construct validity of the ROLS metrics was examined in twelve Division I women's basketball players during pre-season in preparation for their exercise training program. The subjects were categorized based on their injury history during the season: (Group 1) No reported injuries throughout the season, (Group 2) lower limb injury that did not result in missing any games, and (Group 3) lower limb injury that resulted in missing both practice and the remainder of their season. Significant differences were found in ROLS metrics at pre-season between Group 3 and other groups in a prospective cohort study ( p < 0.05). Study findings provided pilot data for supporting ROLS as a measure of postural stability impairment and potential risk for lower limb injury in athletes.